Effect of Different Concentrations and Combinations of Benzyl Aminopurine and Indole-3-Butyric Acid on Micropropagation of Vanilla Planifolia - Khun, Sokhai; Heng, Chenda; Rien, Sothea; Rien, Sinet; Srean, Pao (Journal of Tropical Biodiversity and Biotechnology, 2024)
Micropropagation of explants in vitro has potency to address propagule demands for promoting large-scale vanilla production. Plant growth regulators (i.e., cytokinin, auxin) are necessary for the plant micropropagation success. Objective of this study is to determine the shoot multiplication and root development of Vanilla planifolia under the influence of different concentrations and combinations of BA and IBA for micropropagation. Sixty stem nodal segments of Vanilla planifolia were cultured on MS medium supplemented with IBA (0, 0.5, or 2.0 mg/L) and combined with BA (0, 0.5, 1.0, or 2.0 mg/L). Shoot multiplication and root induction were measured after 60 days of culture. The results show that the MS medium with 1 mg/L IBA hindered shoot growth, while the medium containing 1 mg/L BA yielded the highest number or weight of shoots per explant. For the root development, supplementing the medium with 0.5 mg/L or 1 mg/L IBA improved root length or number of roots per explant, respectively. This research establishes a valuable approach for vanilla micropropagation by utilising low concentrations of plant growth regulators and a rapid protocol. This paves the way for significant advancements in large-scale commercial production.